Pengaruh Viral Marketing Terhadap Purchase Intention Melalui Brand Equity Pada Kampanye Inclusive Beauty MS Glow For Men - Nabilah Ramadhan; Ratih Hurriyati; Puspo Dewi Dirgantari (Coopetition : Jurnal Ilmiah Manajemen, 2023)
Viral marketing is a tactic used in digital marketing to spread information about a product over the internet. MS Glow For Men uses viral marketing tactics in its inclusive beauty campaign through the hashtag #alljugabisa and appoints brand ambassadors who are considered eccentric. The purpose of this research is to see whether the viral marketing conducted by MS Glow For Men is able to influence consumers' purchase intentions either directly or through brand equity mediation. Data were collected through questionnaires which were distributed to 120 respondents of customers and prospective customers of MS Glow For Men through purposive sampling. The results of data processing show that the direct effect of viral marketing on purchase intention (0.491) is greater than the indirect effect of viral marketing on purchase intention through brand equity (0.399)